How Does an Organisation, Based on a Doubling of Load over the Next Ten Years, Assess a Suppliers Readiness to Meet that Load Growth? - Marriott, Andrew (2012)
Many manufacturing organisations have experienced failing supply chains for a period of time. With supply chains currently failing when the volumes or low, how are those supply chains going to deliver what the customer requires when the demand doubles. This type of scenario is one currently facing Rolls Royce as predict a doubling of their civil large engine business over the next five to ten years as shown in figure 1. Any organisation that is predicting this type of growth needs to understand the implications of what that load growth is doing to their supply chains. For many dominant organisations the visibility they will have for viewing a supplier load profile currently will be restricted to the normal S&OP planning parameters, which is normally three years. For those dominant organisations which are predicting load growth this three year visibility of a supplier load may not be long enough for the supplier to take actions to put the correct level of resources in place to meet the load. Many dominant organisations will conduct quite a number assessment to try and determine if suppliers have what they need to meet the load. The main issue with these assessments is that they are only looking at the short term. None of the assessments will review any key aspects in any get detail. An example of this is where there is lack of in depth reviews between the dominant organisation and supplier around load and capacity planning. The lack of these reviews is one of the main reasons why suppliers are failing to meet the customer requirements. However, short term load and capacity planning is not the answer, as that approach is being reactive, rather being proactive. Dominant organisations need to develop a process where they can share supplier load profile over a longer period than they currently do today. Sharing this type of information will allow the dominant organisation to work with their suppliers to make sure that they have the correct resources in place to meet the load profiles going forward. Having the right resources in place at the right time is not just people related. Resources can mean required funds to purchase new capital equipment to grow an organisations capacity, through to possibly growing the organisations footprint by building a new bigger facility. Any of these activities to grow capacity takes significant amounts of time. With this in mind it more imperative for dominant organisations to share demand information beyond the normal S&OP planning parameters. Although organisations will conduct several types of assessments with their suppliers in an attempt to make sure that the suppliers has all the resources in place to meet the load. There is one major area which those assessments fail to cover in any depth, and that is of load and capacity planning. This failure of dominant organisations to review suppliers load and capacity on a regular basis is one of the main reason suppliers are failing to delivery currently. Dominant organisation need to have a process in place that which compiles a supplier’s load profiles for the ten years. From those views of a suppliers load profile then dominant organisation can then have meaningful dialogue about what the actions needs to be completed to enable the supplier to meet the predicted load profiles. Dominant organisations will find that by combining several pieces of information together that they will then be able conduct some rough cut planning to produce the necessary load profiles for their suppliers. However, for meaningful dialogue to take place between dominant organisations and suppliers around load growth there needs to be structured approach adopted. Such a structure needs to be very much geared around load and capacity planning very much like that of dominant organisations own manufacturing facilities.